Two versions of short-term phytoplankton ecophysiology and taxonomic assemblages in the Arctic Ocean’s North Water (Canada, Greenland) - Joli, Nathalie; Lacour, Thomas; Freyria, Nastasia; Royer, Sarah-Jeanne; Babin, Marcel; Lovejoy, Connie (Journal of Plankton Research, 2021)
International audience Abstract Photosynthetic performance in open marine waters is determined by how well phytoplankton species are adapted to their immediate environment and available light. Although there is light for 24 h a day during the Arctic summer, little is known about short-term (h) temporal variability of phytoplankton photosynthetic performance in Arctic waters. To address this, we sampled the North Water (76.5°N) every 4 h over 24 h at two stations on the East and West sides that are influenced by different water masses and current conditions. We specifically investigated phytoplankton pigments, the xanthophyll cycle (XC), which is an indication of photoprotective capacity, and photosynthesis–irradiance (PE) response curves, at the surface and 20 m depth. The photophysiological parameters on the two sides differed along with the taxonomic signal derived from accessory pigments. On both sides, surface XC pigments showed high photoprotection capacity with the dinodinoxanthin–diatoxanthin (DD) and the violaxanthin, antheraxanthin and zeaxanthin cycles correlated with incoming radiation. The PE results showed that communities dominated by small flagellates on the western side performed better compared to diatom dominated communities on the eastern side. We conclude that phytoplankton and photosynthetic capacity differed consistent with known hydrography, with implications for a changing Arctic.